To take care of those on the front line against Covid-19: Is it possible to limit medical liability?. Issue 4 (July 2020) - Tozzo, Pamela; Politi, Caterina; Gabbin, Andrea; Caenazzo, Luciana
Abstract: In the context of the COVID-19 pandemic, it is important not to forget, when the emergency is controlled or even over, that those who today are defined in all Countries as "heroes" could in the future be called to answer for alleged damage from professional liability. It is necessary to be prepared, both as health professionals and from a legal and governmental point of view, for a surge of professional liability claims which, with high probability, will begin to emerge in the coming months.